Duration of On-Campus Academic Engagements of Student Teachers in Finland and Norway. Issue 2 (3rd April 2017) - Christophersen, Knut-Andreas; Elstad, Eyvind; Juuti, Kalle; Solhaug, Trond; Turmo, Are
ABSTRACT: The duration of on-campus academic engagements is an uncertain and highly debated indicator of study input. Researchers adopt this indicator with the expectation that student teachers must invest an amount of time and effort in their courses that more or less equals a normal workweek. In the present empirical study, we examine factors influencing the duration of student teachers' on-campus academic engagements in Norway and Finland using survey data (n = 567). While the teaching profession is highly respected in Finland, and universities make selections for teacher education programs, the profession has a relatively low status in Norway. To meet the objectives of this study, we conducted an OLS regression analysis and found that students' self-discipline and perceived study requirements are the most important predictors of the duration of their on-campus academic engagements. In addition, the motivation to achieve a goal is also significant, while no significant effect was found for intrinsic motivation. Finally, the study shows no significant differences between the coefficients for the Norwegian and Finnish variable.